The analysis of collective mindsets: Introducing a New Method of Institutional Analysis in Comparative Research - Pohlmann, Markus; Bär, Stefan; Valarini, Elizangela (Revista de Sociologia e Política, 2014)
This article presents a specific qualitative method – the Collective Mindset Analysis (CMA) – that is applicable within the frame of institutional analysis to map the cognitive and normative institutions at work. The purpose of this paper is to introduce and discuss the method and its methodology as well. The paper will elaborate on how the method is applied to international research and will provide concrete examples drawn from a bigger research project on economic elites in eleven countries. It will demonstrate the steps of interpretation of interview material from this project with the help of CMA, using concrete text sequences. The sequences have been extracted from interviews with Brazilian top managers that were conducted in the context of an international research project. The paper will show, how an institutional approach, that is relying on the sociology of knowledge, can be supported by a method, that helps to reconstruct the cognitive and normative rules in a given culture and to analyze, how these rules are translated in action orientations to solve culturally significant problems. Thus, the method can be a remedy for the shortcomings of institutional analysis in mapping and comparing the knowledge stocks in different cultures and a new tool in international comparative research.